PENANAMAN BUDAYA DISIPLIN PENDIDIKAN DALAM MENINGKATKAN AKHLAKUL KARIMAH SISWA DI MA AL-IKHLAS CIATER - Anub, Jua Nengsih; Ummu Solihat, Nabila; Sohim, Badru (Atta'dib Jurnal Pendidikan Agama Islam, 2024)
This research aims to understand how cultivating a culture of educational discipline can improve students’ morals at MA Al-Ikhlas Ciater. Using a qualitative approach, data was collected through structured and unstructured interviews with madrasa heads, morals subject teachers, and students. The research results show that the personal approach by madrasa heads and teachers, the implementation of special programs such as routine religious lectures and extracurricular activities, as well as the use of educational reward and sanction systems, are very effective in improving students’ discipline and morals. The positive impact of this disciplinary culture can be seen in increasing students’ self-awareness, positive behavior changes, and the internalization of moral values. It is hoped that this research can contribute to the development of more effective educational strategies in improving students’ morals and morals in the madrasa environment.